1997
DOI: 10.1002/(sici)1096-9071(199708)52:4<419::aid-jmv13>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the caliciviruses

Abstract: A phylogenetic portrait of the genus Calicivirus in the family Caliciviridae was developed based upon published sequences and newly characterized calicivirus (CV) strains, including additional Sapporo-like HuCV strains in pediatric diarrhea stool specimens from South Africa, the United Kingdom, and the United States. Distance and parsimony methods were applied to nucleotide and amino acid sequences of human and animal calicivirus 3D RNA-dependent RNA polymerase (approximately 470nt) and capsid hypervariable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 20 publications
(26 reference statements)
0
49
0
1
Order By: Relevance
“…2. Trees produced for each of the genomic regions evaluated grouped the characterized prototype calicivirus strains similarly to reports of previous phylogenetic analyses (2,4,70). However, phylogenetic classification of the NB virus varied with the genome region evaluated and included placements as a new genus (2C helicase/ATPase), a new SLV genogroup (3C protease), and a new lagovirus genogroup (3D RdRP and VP1 capsid).…”
Section: Genomic Organization Of Bec-nb Virusmentioning
confidence: 99%
“…2. Trees produced for each of the genomic regions evaluated grouped the characterized prototype calicivirus strains similarly to reports of previous phylogenetic analyses (2,4,70). However, phylogenetic classification of the NB virus varied with the genome region evaluated and included placements as a new genus (2C helicase/ATPase), a new SLV genogroup (3C protease), and a new lagovirus genogroup (3D RdRP and VP1 capsid).…”
Section: Genomic Organization Of Bec-nb Virusmentioning
confidence: 99%
“…Human SLVs have also been reported as genetically diverse and classified into 4 genetic clusters, each of which is represented by Manchester/93 (and/or Sapporo/82), Houston/90 (and/or Parkville/94), Stockholm/97 and London/92, respectively [2,18,27,40]. In addition, a porcine enteric calicivirus (PEC) has recently been shown to be related to the SLV genus and to belong to a fifth genetic cluster [15].…”
Section: Introductionmentioning
confidence: 99%
“…A recently developed reverse transcription-PCR (RT-PCR) assay that targets the RdRp (1,2,10,16,26,27) or capsid gene (4,7,9,11,21,22,28,31,33) and phylogenetic analysis revealed that NV is classified into two genogroups, genogroup I (GI) and genogroup II (GII). In a previous study, we proposed a genotyping scheme for NV based on diversity in the capsid N terminus/shell (N/S) gene and reported nine genotypes in GI and 10 genotypes in GII (19).…”
mentioning
confidence: 99%